2019
DOI: 10.1002/anie.201812227
|View full text |Cite
|
Sign up to set email alerts
|

Photoredox‐Catalyzed Site‐Selective α‐C(sp3)−H Alkylation of Primary Amine Derivatives

Abstract: The synthetic utility of tertiary amines to oxidatively generate a-amino radicals is well established, however,p rimary amines remain challenging because of competitive side reactions.T his report describes the site-selective a-functionalization of primary amine derivatives through the generation of a-amino radical intermediates.Employing visible-light photoredox catalysis,p rimary sulfonamides are coupled with electron-deficient alkenes to efficiently and mildly construct CÀCbonds.Interestingly,adivergence be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(51 citation statements)
references
References 41 publications
2
46
0
Order By: Relevance
“…8). 25 Using a trifluoromethylsulfonamide (triflamide) protecting group for the side-chain amine, addition of tert-butyl acrylate at the carbon a to the e-amine was demonstrated. After excitation of an iridium catalyst, single electron oxidation of quinuclidine forms an intermediate capable of performing hydrogen atom transfer (HAT) with the a-carbon, thereby producing the radical anion of the sulfonamide.…”
Section: Polar Amino Acid Side Chainsmentioning
confidence: 99%
“…8). 25 Using a trifluoromethylsulfonamide (triflamide) protecting group for the side-chain amine, addition of tert-butyl acrylate at the carbon a to the e-amine was demonstrated. After excitation of an iridium catalyst, single electron oxidation of quinuclidine forms an intermediate capable of performing hydrogen atom transfer (HAT) with the a-carbon, thereby producing the radical anion of the sulfonamide.…”
Section: Polar Amino Acid Side Chainsmentioning
confidence: 99%
“…Additionally, the installed bis(phenylsulfonyl)ethylene group was a helpful synthetic intermediate for further versatile transformations. Later in 2019, Rovis's group also reported an example of photo-mediated functionalization of the lysine derivative with tert-butyl acrylate in 58% yield with 1:1 dr value (Scheme 9b) [35]. Notably, the authors have tested other Electron-deficient olefins were also investigated as alkylation reagents employed in the photo-mediated C(sp 3 )-alkylation of amino acids.…”
Section: Molecules 2020 25 X For Peer Review 3 Of 41mentioning
confidence: 99%
“…Additionally, the tinstalled bis(phenylsulfonyl)ethylene group was a helpful synthetic intermediate for further versatile transformations. Later in 2019, Rovis's group also reported an example of photo-mediated functionalization of the lysine derivative with tert-butyl acrylate in 58% yield with 1:1 dr value (Scheme 9b) [35]. Notably, the authors have tested other protecting groups such as the trifluoroacetyl group, p-toluenesulfonyl group, and acetyl group, and they are all deleterious to this process, which indicated that the trifluoromethanesulfonyl group as the protecting group on the nitrogen atom was extremely essential to the reaction.…”
Section: Molecules 2020 25 X For Peer Review 3 Of 41mentioning
confidence: 99%
“…In 2019, Rovis and co-workers reported the site-selective -functionalization of primary amines through the generation of -amino radical intermediates (Scheme 59). 56 Employing visible-light photoredox catalysis, primary sulfonamides were coupled with electron-deficient alkenes to form C-C bonds. Interestingly, a divergence between intermolecular HAT catalysis and intramolecular 1,5-HAT was observed via accurate manipulation of the protecting group.…”
Section: Short Review Syn Thesismentioning
confidence: 99%